Case report: Clinical features and management outcomes of isolated corneal intraepithelial neoplasia - Al-Swailem, Samar A.; Alkatan, Hind M.; AlDhaheri, Huda Saif; AlHilali, Sara M.; Maktabi, Azza M. Y. (Frontiers in Ophthalmology, 2024)
Purpose: To report clinical features and treatment outcome of three cases with isolated corneal intraepithelial neoplasia (CIN).Methods: This case series presents 3 patients with isolated CIN. Data collected included, presenting signs and symptoms including vision, anterior segment examination, medical and surgical outcomes and signs and symptoms at lost posttreatment visit.Results: Case 1 was a 45-year-old male who presented with an isolated grayish amoeboid corneal lesion which was excised with alcohol assisted epitheliectomy, he also received 6 cycles of topical mitomycin C (MMC) 0.02% and one injection of interferon alfa-2b with no recurrence during the 10-year follow-up period. Case 2 was 78-year-old male referred for a suspicious white corneal lesion which was completely excised, the patient also received 6 subconjunctival injections of interferon alpha-2b.However, the lesion recurred at 2.5-years post-treatment. Case 3 was a 63-year-old male patient who presented with an isolated corneal lesion that was excised using alcohol-assisted epitheliectomy, patient received four cycles of topical 5-fluorouracil with no recurrence at last follow-up visit at 6 months. Conclusion: Isolated corneal intraepithelial neoplasia (CIN) is a rare entity with few reported cases in the literature. In this case series, we report long and short-term management outcomes of combined surgical and medical therapy for isolated CIN.